Collaborative investigation of the AutoMicrobic System Enterobacteriaceae biochemical card. - Isenberg, H D (1980)
The Enterobacteriaceae biochemical card used in six separate laboratories to identify 170 representatives of Enterobacteriaceae. The AutoMicrobic System (Vitek Systems, Inc.) performed with an accuracy of 97.8% as compared with 98.1% by the standard method selected and 97.6% by a commerically prepared manual system approach. During this time, 5,450 clinical isolates belonging to Enterobacteriaceae were analyzed. Compared with the routine methods used in the various laboratories, the AutoMicrobic System identified 96.4% correctly